DISTORSI BENTUK IMAJINER UNTUK PENCAPAIAN HARMONI - I Made Bendi Yudha (FBS UNY, 2009)
Art is an expression of feeling and soul. It is the crystallization of anidea that derives from imaginative soul experience through observation, deepthinking on the phenomena of social environment. Then, through intellectualability and internal or external motivation raises an intuitive vibration thatstimulates inner emotion to be artistically expressed through the language ofvisual art work.For Balinese, rerajahan is one of literature works which has a valueand symbolic meaning of the all life aspects both on macro and micro cosmos.It is also depicting the energy that is a symbol of gods and evil character.These all are the reflection of dualistic. These concepts which are overlappingand interdependent to each other must be kept appropriately in order tomaintain the harmony.The concept of harmony that exists in rerajahan seems neglected oreven left behind when we compare with the phenomena life in society. Thiscan be seen on the inappropriate acts either to the nature or human life. As weknow, an exploitation of natural resources, the inappropriate authority acts ofparticular parties or people, gender, discrimination on law and human rights,and inappropriate acts of state administration.These phenomena generally make the increase of ecological crisis andthe degradation of human moral or get the level of social poverty even worse. Atpresent, these inappropriate acts are getting out of control because the spreadtakes place both on the low and elite levels. So, these are very complexphenomena just like a messy thread that needs to be solved holistically. Thecomprehension of all the above values have brought some ideas regarding on thelife meanings in which its philosophical concepts in an abstract way astatically areimplemented into the painting art work by combining both the representative andabstractive concepts. It is also implemented in term of applying varied line, color,and textures. It is hope that impasto technique can represent certain symbol andmeaning in order to give the value of the authenticity of the art work which has anartistic personal values and novelty.Key word : Painting art work, distortion of imaginary shape and harmony